Teacher Strategies to Improve Early Childhood Social and Scientific Intelligence in Madani Islamic Kindergartens - Musafir, Musafir; Hamdani, Muh; Muhajirin, Muhammad (Jurnal Ilmiah Mandala Education (JIME), 2024)
This research aims to find out what strategies and obstacles are found in developing children's social intelligence in Madani Islamic Kindergarten. The research method used is qualitative. The data collection techniques used are participatory observation, in-depth interviews and documentation. Next, the data is analyzed using the stages of data condensation, data display and verification. The results of the research show that the teacher's strategy in developing children's social intelligence in Madani Islamic Kindergarten is by example and habituation in instilling responsibility in carrying out activities, discipline in playing and learning, cooperation between students, mutual respect and spontaneous activities in every activity in learning. Developing social intelligence in children is also done by providing continuous motivation in fun activities. Providing motivation is not only in the realm of motivational words or phrases, but places more emphasis on real behavior that is carried out every day. The obstacles found in developing children's social intelligence are a lack of social and cooperative skills, as well as a decrease in aspects of generosity and empathy in students.